Overview Of Nurses' Knowledge About Wound Care With The Moist Wound Healing Method In Hospitals Elisabeth Medan - Vina Yolanda Sari Sigalingging; Ernita Rante Rupang; Helinida Saragih; Haposan Tua Sipahutar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Proper wound care will accelerate wound healing. Where the impact/complications of the wound can damage the physiology of the skin in the patient. Therefore, wound care techniques are one of the supporting factors in accelerating wound healing and restoring skin physiology by using moist wound healing techniques, which can help heal wounds more effectively. In this case, nurses are required to have knowledge about wound care using the moist wound healing method in hospitals. The purpose of the study was to identify nurses' knowledge about wound care using the moist wound healing method at Elisabeth Hospital Medan in 2022. Methods: The research method used was descriptive research. The sampling technique used total sampling technique, with a total sample size of 31 respondents. Data were collected using a questionnaire of nurses' knowledge about wound care using the moist wound healing method. Results: The majority of nurses' knowledge is sufficient as many as 18 people (58.1%) but there are still as many as 7 people (22.6%) who have less knowledge about this method. Conclusion: It is hoped that nurses can better understand and apply the moist wound healing method to improve the quality of service at Elisabeth Hospital Medan.